Impact of vitamin D on glycemic control and microvascular complications in type 2 diabetes: A cross-sectional study. - Salma Ahi; Amirreza Reiskarimian; Mohammad Aref Bagherzadeh; Zhila Rahmanian; Parisa Pilban; Saeed Sobhanian (PLoS ONE)
Vitamin D has been increasingly recognized for its potential role in modulating various health conditions, including diabetes and its complications. Despite growing evidence suggesting that adequate vitamin D levels may reduce the risk of developing type 2 diabetes and its associated microvascular complications, the precise nature of this relationship remains unclear. This study aims to elucidate the connection among vitamin D status, glycemic control, and microvascular complications in patients with type 2 diabetes, thereby highlighting the importance of vitamin D in diabetes management.This analytical cross-sectional study included 199 type 2 diabetic mellitus (T2DM) patients from the Jahrom city endocrinology clinic. Serum 25(OH)D levels were measured, and their microvascular complications (microalbuminuria, retinopathy, neuropathy, macroalbuminuria) and glycemic control (HbA1C) were measured and confirmed according to ADA guidelines and endocrinologist supervision. All analysis were done with SPSS software. The study enrolled 199 type 2 diabetic patients with a mean age of 56.79 ± 10.8 years, of which 63.3% were female and 57.3% had hypertension. The mean BMI was 28.91 kg/m², and 29.1% of participants had vitamin D deficiency. The prevalence of microvascular complications was 25.6% for retinopathy, 14.1% for neuropathy, and 40% for nephropathy. Vitamin D deficiency was notably higher among patients with retinopathy (37.25%), neuropathy (50%), and macroalbuminuria (56.25%). Patients with neuropathy and retinopathy had significantly lesser serum 25(OH)D concentrations compared to patients without these complications. There was a slight inverse correlation between vitamin D levels and both the urine albumin creatinine ratio (r = -0.175, p = 0.018) and HbA1C (r = -0.19, p = 0.007). Although the link between vitamin D levels and retinopathy was not statistically significant (η = 0.903, p = 0.68), the alteration in vitamin D levels was suggestively linked with neuropathy (η = 0.975, p < 0.001).Vitamin D deficiency is prevalent among type 2 diabetic patients and is related to a higher occurrence of microvascular complications and poorer glycemic control. These findings underscore the potential importance of managing vitamin D levels in reducing complications and improving diabetes outcomes. Future studies should investigate whether oral vitamin D supplements consumption can improve glycemic control and reduce microvascular complications in these patients.